Systematization of nursing assistance: implementation in an intensive care uni - Ana Paula Cândido de Oliveira; Maria Eugênia Alves Almeida Coelho; Vitória de Cássia Félix de Almeida; Kênya Waléria de Siqueira Coelho Lisboa; Antônio Lucimilton de Sousa Macêdo (Rev Rene, 2012)
The Systematization of Nursing Assistance gains more importance in the health scenario every day. Keeping in mind the relevance of the use of the nursing process, the description of the experience implementation of the Systematization of Nursing Care in an Intensive Care Unit was carried out. For that we chose a qualitative approach with emphasis on action research. Three nurses and eight nurse technicians of the Intensive Care Unit of a referral hospital in in Crato-CE participated in the experience. Data was collected from the observation guide. There was readiness, including the opening of the institution for the introduction of the nursing process, and also difficulties, such as the opposition of the Nursing technician to the introduction of new instruments. Despite the obstacles, the results showed viability of this practice in implementing the Nursing Process, with consequent professional growth, recovery and greater autonomy to nursing.